2010
DOI: 10.1002/icd.679
|View full text |Cite
|
Sign up to set email alerts
|

Maternal depression and dyadic interaction: the role of maternal attachment style

Abstract: Maternal mental health and the contents of her representational world are important determinants of early parent-child relationship. We examined, first, the role of prenatal and postnatal depressive symptoms and maternal attachment style in predicting the quality of mother-child interaction. Second, we analysed whether the secure-autonomous attachment style can protect the dyadic interaction from the negative effects of maternal depression. The participants were 59 mother-infant pairs examined during pregnancy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
55
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(70 citation statements)
references
References 62 publications
12
55
0
1
Order By: Relevance
“…First, it is consistent with the way previous studies have dealt with missing data of multiple assessment points (e.g. Flykt et al, 2010;Conners, Grant, Crone & Whiteside-Mansell, 2006). Additionally, Little's MCAR test was not significant ( 2 = 44.15, p = ns), which indicates that the data was missing completely at random and therefore suitable for imputation.…”
Section: Parents' Mental Health and Parent-baby Interactions 11supporting
confidence: 86%
See 2 more Smart Citations
“…First, it is consistent with the way previous studies have dealt with missing data of multiple assessment points (e.g. Flykt et al, 2010;Conners, Grant, Crone & Whiteside-Mansell, 2006). Additionally, Little's MCAR test was not significant ( 2 = 44.15, p = ns), which indicates that the data was missing completely at random and therefore suitable for imputation.…”
Section: Parents' Mental Health and Parent-baby Interactions 11supporting
confidence: 86%
“…However, a few recent studies (e.g. Flykt et al, 2010;;Sidor et al,2011) have similarly failed to find such associations. These studies suggested that factors such as chronicity and severity of depression and the additive effect of other risk factors (e.g.…”
Section: Parental Mental Health and Parent-infant Interactionsmentioning
confidence: 92%
See 1 more Smart Citation
“…Mother-child interactions in the presence of PPD may be characterized simultaneously by hostility and unresponsiveness [31,32]. Stein et al [33] proposed that a woman's self-preoccupation and rumination may be a critical process in understanding the effects of PPD on responsive parenting.…”
Section: Secondmentioning
confidence: 99%
“…Thus, parents may adopt intrusive and insensitive child-rearing practices, typical of persons with preoccupied attachment styles, or may easily withdraw from dyadic interactions, typical of persons with avoidant attachment styles (Flykt, Kanninen, Sinkkonen, & Punamäki, 2010; Van Ee, Kleber, Jongmans, Mooren, & Out, 2016). A qualitative study confirmed that parental refugee trauma disturbed children’s creation of secure attachments because the parental fears were overwhelming (De Haene Grieten, & Verschueren, 2010).…”
Section: Introductionmentioning
confidence: 99%